Economic impact of international gender agreements on the labor market of the Republic of Kazakhstan - Mubarakov, Y.Y.; Bordiyanu, I.V.; Kapelyuk, S.D. (BUKETOV BUSINESS REVIEW, 2024)
Object: To study the economic impact of international gender agreements on the labor market in Kazakhstan, identify existing barriers to their implementation and formulate recommendations to improve gender equality and strengthen the country's economic performance. Methods: Analysis of specialized scientific literature and legal framework, theoretical and practical methods of research, generalization and forecasting. Results: The analysis of the implementation of international agreements on gender equality in Kazakhstan revealed certain trends. There had been improvements in women’s access to education and representation in politics, but challenges remained with regard to equal employment opportunities, which required additional efforts to ensure real gender equality. Conclusions: Over the past three years, Kazakhstan has made significant progress in ensuring equal opportunities in education, health and the labour market. However, certain difficulties have been identified in the implementation of international agreements, which the authors are trying to analyse. The article offers concrete ways to improve gender policy in Kazakhstan — a list of priority measures that, in the opinion of the authors, will significantly improve the current situation in this field.